HAK PENDIDIKAN PEREMPUAN MENURUT FUQAHA’ SYAFI’IYAH DENGAN PERSPEKTIF GENDER - Riyadhi, Baidhillah; Asyari, Farida (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2020)
With all the potential capital God gave, it is believed that man will be able to carry out his duties well. Then it is normal for God to place man as ' masterpiece ' of His own universe.     In Shari'ah there is always a balance between the vertical and horizontal dimensions, the ideal and the realistic side, the constant doctrine (the Sabbath) and the Elastic (Murunah), the interests of the world and the Hereafter, the aspect of birth and the inner, interest of individuals and society, and Etc. The principle of benefit is no less important than the principle of balance. This remembers that it was the cause of the point-of-decline, the takeoff and the final goal in the formulation of a law (Maqashid Syari'ah). This research uses qualitative research methods by examining the Library Research related to the opinions of scholars ' followers of Imam Shafi'i on gender issues. Conclusion of the study: women have the same learning opportunities as men, both in material and learning methods, to achieve what is the essential goal of the education process. That is to achieve the perfection of the Insani that comes down to the self-approach (Taqarrub) to God and the realization of happiness in the world and the hereafter.